Outcome of kospen weight management program and association between weight loss, blood pressure and blood glucose among female participants in Terengganu - Noor, Noraznira Mohd Noor (2018)
Background: The National Health and Morbidity Survey (NHMS) 2015 reported that the prevalence of overweight among Malaysian increased from 29.4% in 2011 to 30.0%, and obesity increased from 15.1% in 2011 to 17.7%. The Komuniti Sihat Perkasa Negara (KOSPEN) was introduced in 2013, which emphasises on community empowerment in preventing the Non-Communicable Diseases (NCD). Objective: The objectives of this study were to determine the proportion of successful weight loss (achieved weight loss > 5% from baseline), to compare weight, blood pressure and blood glucose level before and after the six-months program and to determine the association between weight loss with blood pressure and blood glucose among female participants of KOSPEN Weight Management Program in Terengganu. Methodology: This was a cross sectional study conducted from February until April 2018 using secondary data involving seven out of eight districts in Terengganu. The data was obtained from the Terengganu State Health Department KOSPEN Weight Management Program Database for the year 2017 and participants log book. The information was transferred to proforma which then was exported from Excel to SPSS v.24 for analysis. Results: In 2017, there were 125 female participants who took part in this KOSPEN Weight Management Program and 123 participants were included in this study. Descriptive analysis, Paired t-test and simple linear regression was conducted. In this six-months program, 105 (85.4%) of the women lose weight, 4 (3.3%) maintained their weight while 14 (11.4%) gained weight. The mean weight loss was -3.62 kg (3.46). The maximum weight loss was -21.8 kg and the maximum weight gain was 5.2 kg. One-third of the women (n=42) had successful weight loss at six-months post program. Analysis on weight, blood pressure and blood glucose at six months (mean difference, 95% CI) revealed that the mean weight reduced by -2.93 kg (2.27 to 3.60, p<0.001), systolic blood pressure reduced by -1.44 mmHg (-0.54 to 3.42, p=0.153), diastolic blood pressure reduced by -2.04 mmHg (0.71 to 3.37, p=0.003) and blood glucose reduced by -0.25 mmol/L (0.09 to 0.42, p=0.003). Unfortunately, there was no significant association between weight loss and SBP (p=0.894), weight loss and DBP (p=0.518) and weight loss and blood glucose (p=0.524). Conclusion: This study provides the evidence that the KOSPEN Weight Management Program had shown to reduce the NCD risk factors, particularly weight, blood pressure and blood glucose. It can be assumed that this program may have successful in instilling self-awareness about healthy lifestyle and weight loss initiative, leading to individualized behavioural modification among its female participants in Terengganu. Hopefully, continuous partnership with Jabatan Kemajuan Masyarakat (KEMAS), Jabatan Perpaduan Nasional dan Integriti Negara (JPNIN), community leaders and volunteers would improve and make this initiative sustainable.